Fear of Backlash Moderates Female Senior Executives' Communion (but Not Agency) as Compared to Female Lecturers - Tan, Xiao; Zuo, Bin; Wen, Fangfang; Xie, Zhijie; Song, Shijie (Frontiers in Psychology, 2021)
Today, many women work in occupational roles that have once been dominated by men (e.g., senior business executives). However, expectations on senior executives to be agentic (e.g., assertive, dominant) may conflict with prescriptive stereotypes about women to be communal (e.g., helpful, warm). According to this double-bind dilemma, female senior executives get criticized for lacking either agency or communion as both dimensions can be perceived as posing a tradeoff. We hypothesize that female senior executives report higher levels of agency and lower levels of communion than women in a more neutral role (e.g., lecturers) due to the perceived requirements of these occupational roles. In Study 1, N = 212 students rated adjectives on their desirability for men vs. women in Chinese society. They rated agentic characteristics as more desirable for men and communal characteristics as more desirable for women. Studies 2 and 3 used this material. Study 2 randomly assigned N = 207 female students to the role of a senior executive vs. lecturer. Study 3 was conducted with N = 202 female role occupants (96 senior executives, 106 lecturers). As expected, female senior executives reported higher levels of agency and lower levels of communion than female lecturers in both studies. Some women may be particularly aware of the above-mentioned double-bind dilemma and may be more worried about potential backlash than others. They may attempt to reconcile occupational demands (i.e., higher agency, lower communion) with prescriptive gender stereotypes (i.e., lower agency, higher communion). We therefore explore whether fear of backlash attenuates the effect of women’s role type (senior executives vs. lecturers) on agency and communion. Indeed, we found that senior executives who were particularly worried about backlash reported almost as much communion as lecturers did. In contrast, senior executives consistently reported higher levels of agency than lecturers regardless of their fear of backlash. The present study documents prescriptive gender stereotypes in China, how women differ as a function of their occupational roles, and how fear of backlash may motivate female senior executives to reconcile having high levels of both agency and communion.